Botanical drugs for treating erectile dysfunction: clinical evidence - Xu, Dengjianyi; Zhang, Yucong; Bai, Jian; Yuan, Huixing; Wang, Tao; Liu, Jihong; Song, Wen; Ma, Delin (Frontiers in Pharmacology, 2023)
Phosphodiesterase-5 inhibitors (PDE5-i) have been widely used in clinical practice for the treatment of erectile dysfunction (ED). However, due to its suboptimal therapeutic effects and side effects, it is necessary to develop new medicines for ED treatment. Botanical drugs have been widely investigated as potential ED treatment drugs and have shown promising therapeutic effects. This review summarized 34 studies, including 5 botanical drugs with PDE5 inhibitory activity, 7 botanical drugs without PDE5 inhibitory activity, and 6 mixed botanical drugs. The results of clinical studies regarding the aforementioned botanical drugs and relevant mechanisms are summarized in this study. It is necessary to conduct high-quality clinical trials to verify the dosage, targeted patients and therapeutic effects, and further pharmacology experiments are also needed to identify the active compounds.